Mahmūd Sa’īd Mamdūẖ Method in Hadith Judging from the book al-Ta’rīf bi Awhām Man Qasama al-Sunan ila Șahih wa Ḍa’if | منهج محمود سعيد ممدوح في الحكم على الحديث من خلال كتاب التعريف بأوهام من قسم السنن إلى صحيح وضعيف - Ahmad Dahlan (Al-Zahra : Journal for Islamic and Arabic Studies, 2015)
This paper discusses  Mahmūd Sa’īd Mamdūh method in criticizing works Albānī in hadith field.  By analyzing the book al-Ta'rīf bi Awhām Man Qasama al-Sunan ila Șaẖiẖ wa Ḍaif, chapters 1, the book of fasting traditions seem that Mamdūẖ accept all kinds of hadith narrators weak as long as there is no assessed lies, using more concise wording traditions and see justice narrator of zahir become Muslim. Mamdūẖ adhered to al-Ujali and Ibn Hibban reference, further Mamdūẖ narrator tends to reinforce the disputed status as companions of the Prophet. He also received hadiths from narrators unknown in Jarh wa ta'dil and use weak hadiths in legal matters of fiqh